Association of Antibiotic Alterations in Gut Microbiota With Decreased Osseointegration of an Intramedullary Nail in Mice With and Without Osteomyelitis - Zhao, Xingqi; Zhang, Zhaohui; Wang, Yiran; Qian, Kai; Qin, Hanjun; Wan, Haoyang; Wang, Shihao; Zhu, Zhengwen; Yang, Siqi; Jiang, Nan; Zhang, Yifang; Bai, Yang; et al. (Frontiers in Endocrinology, 2021)
Treatment of osteomyelitis requires prolonged antibiotic therapy which significantly alters the gut microbiota. While the influences on bone mass and microstructure have been extensively studied, it is poorly understood what impact the changes in gut microbiota may have on the host response to osseointegration around an intramedullary nail implanted. Here, we explored the influence of gut microbiota on the bone osseointegration process around an implant under two conditions: implantation of an intramedullary nail in the bone marrow cavity and chronic osteomyelitis (CO) induced by Staphylococcus aureus infection. Body weight, hepatorenal functions, serum levels of proinflammatory cytokines were monitored. The composition of gut microbiota was assessed via 16S rRNA sequencing, and the bone condition was analyzed via micro-computed tomography, hematoxylin and eosin staining, safranin O-fast green and Goldner’s trichrome staining. Osteoblastogenesis and osteoclastogenesis were assessed by detecting tartrate-resistant acid phosphatase and osterix expression. We found that perturbation of gut microbiota (increase in Proteobacteria and decrease in Bacteroidetes) associated with delayed osseointegration and increased levels of proinflammatory cytokines in the serum (p<0.05), lower bone mass (p<0.05), deficient endochondral ossification and bone formation, reduced osteoblastogenesis (p<0.05) and enhanced osteoclastogenesis (p<0.001). Survival rates (p=0.002) and bacterial loads (p=0.0363) in bone differed significantly between the CO and antibiotic-treated CO mice, but cytokines levels, bone mineral density, and bone formation did not differ, likely because of the severely damaged bone structure. In summary, antibiotic treatment perturbed the gut microbiota and significantly interfered with the bone osseointegration around the nail by increasing proinflammatory cytokine levels in circulation, inhibiting osteoblastogenesis, enhancing osteoclastogenesis, and thus leading to higher pathogen colonization as well as higher mortality postinfection. This report of ours is the first to demonstrate antibiotic-induced alterations in the gut microbiota affect bone osseointegration, helping us understand the role of gut microbiota disorders in osteoblastogenesis and osteoclastogenesis following implant insertion with or without infection.